High‐Electron‐Mobility and Air‐Stable 2D Layered PtSe2 FETs. Issue 5 (25th November 2016) - Zhao, Yuda; Qiao, Jingsi; Yu, Zhihao; Yu, Peng; Xu, Kang; Lau, Shu Ping; Zhou, Wu; Liu, Zheng; Wang, Xinran; Ji, Wei; Chai, Yang
Abstract : The electrical and optical measurements, in combination with density functional theory calculations, show distinct layer‐dependent semiconductor‐to‐semimetal evolution of 2D layered PtSe2 . The high room‐temperature electron mobility and near‐infrared photoresponse, together with much better air‐stability, make PtSe2 a versatile electronic 2D layered material.